Did quantitative easing affect interest rates outside the US? New evidence based on interest tate differentials - Ansgar Belke; Daniel Gros; Thomas Osowski (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
This paper explores the effects of non-standard monetary policies on international yield relationships. Based on a descriptive analysis of international long-term yields, we find evidence that long-term rates have followed a global downward trend prior to as well as during the financial crisis. Comparing interest rate developments in the United States and the Eurozone, it appears difficult to find a distinct impact of the Fed's QE1 on US interest rates for which the global environment - the global downward trend in interest rates - does not account. Motivated by these results, we analyze the impact of the Fed's QE1 program on the stability of the US-Euro long-term interest rate relationship by using a CVAR and, in particular, recursive estimation methods. Using data between 2002 and 2014, we find limited evidence that QE1 caused a breakup or a destabilization of the transatlantic interest rate relationship. Taking global interest rate developments into account, we thus find no significant evidence that QE had an independent, distinct impact on US interest rates. – – Der vorliegende Artikel untersucht die Auswirkungen unkonventioneller geldpolitischer Maßnahmen auf internationale Zinsbeziehungen. Aufbauend auf einer deskriptiven Analyse ergeben sich Hinweise, dass die weltweite Entwicklung der Langfristzinsen vor und während der Finanzkrise von einem globalen Abwärtstrend geprägt war. Unter Berücksichtigung dieser trendmäßigen Zinsreduktionen lässt sich im Rahmen eines Vergleichs der europäischen und amerikanischen Zinsentwicklungen kein separater Effekt des 'Quantitative Easings' der Federal Reserve auf den amerikanischen Zins erkennen. Ausgehend von diesem Ergebnis werden empirisch im Rahmen eines kointegrierten vektorautoregressiven Models ('CVAR') die Auswirkungen des 'QE1'- Programms auf die Stabilität der Beziehung zwischen europäischem und amerikanischem Langfristzins untersucht. Die Ergebnisse der Analyse generieren nur geringe Hinweise, dass 'QE1' zu einer Destabilisierung bzw. einem Zerfall der transatlantischen Zinsbeziehung geführt hat. In dieser Hinsicht ergeben sich keine signifikanten Hinweise darauf, dass das 'Quantitative Easing' der Federal Reserve einen unabhängigen bzw. separaten Einfluss auf den amerikanischen Langfristzins hatte.
Keywords: C32; E43; E44; E58; F31; G01; G15; 330; quantitative easing; unconventional monetary policies; time series econometrics; Cointegrated VAR (CVAR); recursive methods